Tourism Education Awareness Of Social Studies In Saudi Arabia - Jaber, Humoud Mohammed A (2020)
Tourism Education Dimensions being regarded as an essential tool to improve awareness of tourism among students. This study aims to analyze the tourism educational awareness of social studies in Saudi Arabia by investigating the tourism education dimensions process in social studies curricula in intermediate and secondary schools.